2010
DOI: 10.1007/s10495-010-0487-7
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine dithiocarbamate (PDTC) blocks apoptosis and promotes ionizing radiation-induced necrosis of freshly-isolated normal mouse spleen cells

Abstract: Ionizing radiation (IR) is a pro-oxidant that kills cells by both apoptotic and necrotic mechanisms. Pyrrolidine dithiocarbamate (PDTC) is a thiol-containing compound that may act either as a pro- or anti-oxidant depending on the experimental conditions. This study was designed to determine whether PDTC would reduce or enhance IR-induced cell death of freshly-isolated normal mouse B6/129 spleen cells (NMSC). We determined the effect of increasing doses of IR, PDTC alone and PDTC followed by IR on the viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…These findings strongly corroborate recent in vitro data on increased efficacy of DHA in Molt-4, glioma and Jurkat T-lymphoma cells when combined with IR [20], [22]. Many kinds of tumor cells have been found to be resistant to IR, hence requiring increased IR dose for cancer treatment, which leads to higher side effects [7]. Our observations that the G2/M arrest induced by treatment with low-dose (2 and 4 Gy) IR for 24 h disappeared at 36 h after treatment (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings strongly corroborate recent in vitro data on increased efficacy of DHA in Molt-4, glioma and Jurkat T-lymphoma cells when combined with IR [20], [22]. Many kinds of tumor cells have been found to be resistant to IR, hence requiring increased IR dose for cancer treatment, which leads to higher side effects [7]. Our observations that the G2/M arrest induced by treatment with low-dose (2 and 4 Gy) IR for 24 h disappeared at 36 h after treatment (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, some investigations demonstrate that, after IR treatment, transcription factors such as NF-κB and p53 upregulate the antiapoptotic proteins Bcl-2 and Bcl-x L through the intrinsic apoptosis pathway [6]. Although it is the most effective modality in cancer treatment, IR, especially the high-dose IR, also provokes lots of side effects on normal tissues such as undesirable inflammatory reactions [6], [7]. Therefore, natural products with lower side effects combined with low-dose IR have received increasing attention in recent years for the discovery of novel cancer therapeutic methods.…”
Section: Introductionmentioning
confidence: 99%
“…5C). Pyrrolidine dithiocarbamate (PDTC) is an effective inhibitor of NF-κB activation and suppresses NF-κB dependent transcription of pro-inflammatory cytokines and chemokines [28]. When CaSki cells were treated with PDTC, the activity of NF-κB p65 decreased and the expression of STC1 down-regulated with increasing time of PDTC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, study by Morais et al (2010) and Zheng et al (2014) showed that, when combined with cisplatin, PDTC significantly induced apoptosis in human cancer cells. On the other hand, study by Thompson et al (2010) has shown that PDTC blocks apoptosis in normal mouse spleen cells. In this study, we found that apoptosis was significantly inhibited in EV71-infected cells when PDTC was added at the early stage of viral replication.…”
Section: Discussionmentioning
confidence: 99%